Жизнь вопреки: [сборник рассказов] / Евгения Михайлова - Михайлова Евгения Анатольевна (Детектив-событие, 2020)
Экземпляры: ф.4 (20211217) / Инвентарный номер: 872 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: М 69 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-445.1